التوافق النفسي الوظيفي أثناءالعودة الطبيعة للتدريس بعد كورونا - بهيليل, ابتسام (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
يهدف بحثنا هذا إلى التعرف على التوافق النفسي – الوظيفي أثناء العودة الطبيعية للتدريس بعد كورونا في دراسة ميدانية لدى عينة من أساتذة مرحلة التعليم الابتدائي، حيث استخدمنا المنهج الوصفي التحليلي لملاءمته مثل هذه البحوث. ولجمع البيانات حول موضوع بحثنا قمنا ببناء استبيان (التوافق النفسي – الوظيفي)، وتطبيقه على عينة مقدارها ( 82 أستاذ وأستاذة)، ولتحليل البيانات استخدمنا برنامج الحزمة الإحصائية في العلوم الاجتماعية (SPSS)، لنتوصل على نتائج البحث التالية: أن أغلب أساتذة التعليم الابتدائي (عينة البحث) كان مستوى توافقهم النفسي – الوظيفي عالي. كما انه لم تُوجد فروق ذات دلالة إحصائية بين الذكور والإناث في الأبعاد الأربع الأولى للاستبيان؛ بينما وُجدت فروق في المتوسط الحسابي بين الأساتذة (ذكور وإناث) في البعدين الرابع والخامس ولصالح الأستاذات الإناث. وأخيرا لم يوجد أثر لمتغير الخبرة المهنية (عالية – متوسطة - منخفضة) على التوافق النفسي – الوظيفي أثناء العودة الطبيعية للتدريس بعد كورونا لدى معلمي المرحلة الابتدائية.
دراسة ميدانية لدى عينة من الاساتذة بمرحلة التعليم الابتدائي
Our research aims to identify psychological-functional compatibility during the normal return to teaching after Corona in a field study among a sample of primary school teachers, Where we used the descriptive analytical approach for its suitability for such research. To collect data on the subject of our research, we built a questionnaire (psychological-functional compatibility), and applied it to a sample of (82 male and female teachers), To analyze the data, we used the statistical package for social sciences (SPSS). To reach the following results of the research: Most of the teachers of primary education (the research sample) had a high level of psychological-functional compatibility. Also, there were no statistically significant differences between males and females in the first four dimensions of the questionnaire; While there were differences in the arithmetic mean between teachers (male and female) in the fourth and fifth dimensions, in favor of female teachers. Finally, there was no effect of the professional experience variable (high - medium - low) on psychological-functional adjustment during the normal return to teaching after Corona among primary school teachers.
Keywords: التوافق النفسي – التوافق الوظيفي – مهنة التدريس – جائحة كورونا; Psychological compatibility - functional compatibility - the teaching profession - the Corona pandemic.